Resveratrol reduces radiation-induced liver damage and fibrosis, and may be related to inhibiting cellular aging and reducing inflammation - Songhui Zhai; He Xu; Jianxin Xue; Lu Gan; Fang Gao; Lijuan Hu (Innate Immunity)
Objective To research whether radiation-induced liver damage and fibrosis could be mitigated by resveratrol (RSV) and to elucidate its underlying mechanism. Methods A radiation-induced liver damage (RILD) model of murine was constructed. RSV was used as an intervention agent. The effects of RSV on inflammatory reaction, apoptosis, senescence, fibrosis, survival, and liver functions were detected by β-Gal, Sirius red, Masson's trichrome, and Tunnel staining using an automated biochemistry analyzer. The protein expression levels of P16 and P21 were detected by Western blot. Results RSV alleviated inflammatory injury of RILD mice. RSV decreased the serum pro-inflammatory cytokines of RILD mice. RSV alleviated radiation-induced hepatocellular senescence. The protein expression levels of P16 and P21 in RILD mice were decreased with RSV administration. RSV decreased the number of apoptotic cells in the early stage of RILD. RSV alleviated liver fibrosis and liver function in RILD mice. Conclusions RSV reduces RILD and fibrosis, and may be related to inhibiting cellular aging and reducing inflammation.